Altered locus coeruleus–norepinephrine function following single prolonged stress. Issue 6 (20th December 2012) - George, Sophie A.; Knox, Dayan; Curtis, Andre L.; Aldridge, J. Wayne; Valentino, Rita J.; Liberzon, Israel
Abstract Data from preclinical and clinical studies have implicated the norepinephrine system in the development and maintenance of post‐traumatic stress disorder. The primary source of norepinephrine in the forebrain is the locus coeruleus (LC); however, LC activity cannot be directly measured in humans, and previous research has often relied upon peripheral measures of norepinephrine to infer changes in central LC–norepinephrine function. To directly assess LC–norepinephrine function, we measured single‐unit activity of LC neurons in a validated rat model of post‐traumatic stress disorder – single prolonged stress (SPS). We also examined tyrosine hydroxylase mRNA levels in the LC of SPS and control rats as an index of norepinephrine utilisation. For electrophysiological recordings, 92 LC neurons were identified from 19 rats (SPS, 12; control, 7), and spontaneous and evoked responses to a noxious event (paw compression) were recorded. Baseline and restraint stress‐evoked tyrosine hydroxylase mRNA expression levels were measured in SPS and control rats (n = 16 per group) in a separate experiment. SPS rats showed lower spontaneous activity but higher evoked responses, leading to an enhanced signal‐to‐noise ratio of LC neurons, accompanied by impaired recovery from post‐stimulus inhibition. In concert, tyrosine hydroxylase mRNA expression in the LC of SPS rats tended to be lower at baseline, but was exaggerated following restraint stress. These data demonstrate persistent changes in LC function following stress/trauma in a rat model of post‐traumatic stress, as measured by differences in both the electrophysiological properties of LC neurons and tyrosine hydroxylase mRNA transcription.